Stock Market Reaction to Dividend Announcement in Indonesian Listed Companies - Dewi, Cynthia Sari (2011)
This study aims to investigate the share price reaction to dividend announcement. It also examines whether or not the cumulative abnormal return (CAR) is affect to by control variables which is dividend change, earning change, dividend yield, normal trading volume, pre-cumulative abnormal return (PRECAR) and firm size). This study uses two methods to estimate the model. The first method is event study and the second method is Ordinary Least Square (OLS) regression. The sample firm utilized the event study and OLS regression are 415 and 243 companies respectively which are listed on the Indonesia Stock Exchange (IDX) during 2006 - 2010. The findings from the event study analysis indicate the share price reaction to dividend announcement is positive for dividend increase and negative for dividend decrease. The OLS regression result shows that the PRECAR variable is positive and significant while the other independent variables are insignificant.